Representações de escrita do sujeito-professor de Língua Portuguesa - Alves, Maria Leuziedna Dantas (2020)
This research has as object of study the discourse about the writing representations of the Portuguese Teacher of High School. To this end, we seek to answer the following questions: What are the conceptions of writing of the teacher subject and possible resignifications? How did the Portuguese language teacher learn to write and what representations constituted by that teacher reflect in his teaching practice? What does this teacher write? And with what purposes does writing use? We list as a general objective to investigate the discourse of the subject-teacher of Portuguese Language about the representations of writing that constitute him personally and professionally and in what way they directly or indirectly influence his teaching practice. The specific objectives were: to analyze, in the teacher's discourse, his conceptions of writing and possible resignifications; to verify, in the teacher's discourse, how he learned to write and what representations constituted by this learning reflect in his teaching practice; identify in the teacher's speech, what he wrote, what he writes and with what objectives. To study this issue, three theoretical axes guided our analysis: the conception of representation in Chartier (2015, 2011, 2002a, 2002b), that of memory in Ricceur (2014) and the notion of dialogism, based on Bakhtin's ideas ( 2015 [1979], 2014 [1975], 2012 [1984]) and Volóchinov (2017 [1929]), about the relationships of otherness, demarcated by the strategies of interaction of the I-for-myself towards the notion of responsive subject and participative of his act immersed in the chronotope. For this, the methodology adopted is focused on a qualitative approach, anchored in ethnographic-based research, having as a data collection instrument the conduct of interviews with semi-structured questions to 15 Portuguese language teachers, with different teaching experiences in the classroom and that they work in education in the city of Sousa-PB, at the state and federal levels, in the High School segment. After analyzing the corpus, we came to the conclusion that, in general, teachers narrate experiences that involve ways of learning to write in basic education, following a monological conception of the word. However, due to academic and professional training, they are revealing resignified features of axiological perceptions that positively value the representation of writing based on the interactionist conception of language. In addition, there are indications that teachers recognize themselves as writers, to the degree that they cite the production of discursive genres in the fields of personal and professional life, accentuated by the need to expose themselves as a competent subject of writing, in an exotopic relationship, to motivate the student in his writing practice. Therefore, through singular experiences, we perceive representations that are opposed to the negative discourse conveyed by the media.These representations of writing reveal a responsive and responsible teaching attitude, detaching themselves from the monological conception, although the speeches do not signal a total break of the traditional model because there are gaps in terms of knowing how to make the interaction in the classroom.